(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Virtual learning environment. Are widely used in education and across many sectors to provide educational content and improve communication. This paper details the results of an internet questionnaire of 248 2nd students at an English seventh college on their usage of online learning environments. The survey looked into to the impact of using the school’s Leon learning, and it has been based on three survey questions: whether using a VLE has a positive impact on student achievement; whether using a VLE in learning and teaching helps students develop independent learning; and whether using a VLE increases students’ incentive to learn. According to the statistically significant findings, using Moodle better learning and motivation to learn, as stated by the participating students. Teachers will be interested in the findings because they indicate out areas where they might focus their efforts in order to encourage the use of VLEs to improve the quality of learning.